2017
DOI: 10.1038/ncomms15143
|View full text |Cite
|
Sign up to set email alerts
|

TNFα drives mitochondrial stress in POMC neurons in obesity

Abstract: Consuming a calorically dense diet stimulates microglial reactivity in the mediobasal hypothalamus (MBH) in association with decreased number of appetite-curbing pro-opiomelanocortin (POMC) neurons; whether the reduction in POMC neuronal function is secondary to the microglial activation is unclear. Here we show that in hypercaloric diet-induced obese mice, persistently activated microglia in the MBH hypersecrete TNFα that in turn stimulate mitochondrial ATP production in POMC neurons, promoting mitochondrial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
111
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(123 citation statements)
references
References 23 publications
11
111
0
1
Order By: Relevance
“…To examine potential alterations in mitochondrial morphology in AIF-deficient POMC neurons, mitochondrial architecture and morphology were analyzed via electron microscopy in POMC neurons from AIF ΔPOMC and control mice both upon NCD- and HFD-feeding conditions (Figure S4A). In line with previous reports (Diano et al, 2011; Schneeberger et al, 2013; Yi et al, 2017), mitochondrial architecture in control animals was altered upon HFD feeding with an increase in mitochondrial area (Figure S4B) and perimeter (Figure S4C), a decrease in maximal cristae width (Figure S4D), and a tendency to decreased mitochondrial-ER contacts (Figure S4F). However, these alterations were attenuated upon AIF deletion in POMC neurons in HFD-fed mice.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…To examine potential alterations in mitochondrial morphology in AIF-deficient POMC neurons, mitochondrial architecture and morphology were analyzed via electron microscopy in POMC neurons from AIF ΔPOMC and control mice both upon NCD- and HFD-feeding conditions (Figure S4A). In line with previous reports (Diano et al, 2011; Schneeberger et al, 2013; Yi et al, 2017), mitochondrial architecture in control animals was altered upon HFD feeding with an increase in mitochondrial area (Figure S4B) and perimeter (Figure S4C), a decrease in maximal cristae width (Figure S4D), and a tendency to decreased mitochondrial-ER contacts (Figure S4F). However, these alterations were attenuated upon AIF deletion in POMC neurons in HFD-fed mice.…”
Section: Resultssupporting
confidence: 92%
“…This study revealed not only enhanced TNF-α expression in the mediobasal hypothalamus in DIO mice, but further demonstrated that TNF-α enhances mitochondrial OXPHOS and complex I expression in POMC neurons alongside with mitochondrial enlargement and increased expression of the mitochondrial fusion factor optic atrophy 1 (Opa1) (Yi et al, 2017). Accordingly, ablation of TNF-α signaling in the mediobasal hypothalamus (MBH) of DIO mice reversed diet-induced alterations in mitochondrial dynamics in POMC neurons and improved energy and glucose homeostasis.…”
Section: Discussionmentioning
confidence: 63%
“…; Yi et al . ). However, in a ROI including the PVN visualized by the mEGFP in Sim1 neurons, the abundance of Iba1 did not increase in the PVN of male Sim1‐Cre:Rosa‐mEGFP mice exposed to HF diet (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…; Dorfman and Thaler ; Yi et al . ). Female rodents exposed to HF diet, while having less severe adverse metabolic consequences than male mice, nevertheless develop obesity.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation